Overview of Streaming Video Profile Amendment in MPEG-4 video standard - Weiping Li (MPEG-4 : proceedings of Workshop and Exhibition on MPEG-4 : June 18-20, 2001, San Jose, California, USA, 2001)
Streaming Video Profile is the subject of an Amendment in MPEG-4. It is developed in response to the growing need on a video coding standard for streaming video over the Internet. It provides the capability to distribute single-layer frame-based video over a wide range of bitrates with high coding efficiency. It also provides fine granularity scalability (FGS) and its combination with temporal scalability to address a variety of challenging problems in delivering video over the Internet. This paper provides an overview of the video coding techniques in this Amendment of the MPEG-4 video standard.